Design of scientific reasoning test instruments on simple harmonic motion topics. Issue 3 (February 2019) - Zafitri, T S; Siahaan, P; Liliawati, W
Abstract: Scientific reasoning is one of the 21st century skills that is expected to be taught in science class. The students scientific reasoning skills are important in addressing new issues and planning investigations to solve real-life science, engineering and social problems. This study aims to design a scientific reasoning test instrument on simple harmonic motion topics in senior high school. The method utilized in this research is a research and development of instructional model 4D (define, design, develop, and disseminate), but this research limited only to 2D (define and design). The define stage include: (1) literature study (2) field study (3) concept analysis (4) formulate instructional objective. The design stage is to design the test instrument to be developed. The test intrument scientific reasoning based on Han (2013). There are 8 dimensions of scientific reasoning that is control of variables, proportions and ratios, probability, correlational reasoning, deductive reasoning, inductive reasoning, causal reasoning, and hypothetical-deductive reasoning. The test instrument scientific reasoning consists of 24 items, two tier, multiple choice test.